(untitled) (JULACE: Journal of the University of Namibia Language Centre, 2018)
Vocabulary, much more than grammar, is the key to any learner to understand what she/he hears and reads in school; and to communicate successfully with other people. For this reason it is very important for a learner to quickly build up a large store of words. Research studies have shown the strong links between having an extensive vocabulary and achieving school success. Lewis (1993) states that “Lexis the core or heart of language”. As English Second Language students develop greater fluency in English it is significant for them to acquire more productive academic vocabulary knowledge and to develop their own personal vocabulary learning strategies. This conceptual paper aims to highlight the academic lexicon gap between English First Language students and ESL students. Moreover, it defines what academic vocabulary is and how vocabulary is learned. Finally it provides effective vocabulary teaching strategies that could be employed in the ESL classroom in order to minimize the lexicon gap between English first language students and ESL students.